2010
DOI: 10.1029/2009pa001735
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology in the Sea of Marmara during the last 23 ka: Implications for timing of Black Sea connections and sapropel deposition

Abstract: Sediments deposited under lacustrine and marine conditions in the Sea of Marmara hold a Late Quaternary record for water exchange between the Black Sea and the Mediterranean Sea. Here we report a multiproxy data set based on oxygen and strontium isotope results obtained from carbonate shells, major and trace elements, and specific organic biomarker measurements, as well as a micropaleontological study from a 14C‐dated sediment core retrieved from the Sea of Marmara. Pronounced changes occurred in δ18O and 87Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
145
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(161 citation statements)
references
References 82 publications
16
145
0
Order By: Relevance
“…The highest values characterize the 1380-980 cm so-called "sapropelic" interval. This organic matter enrichment has been previously reported in the different basins of the Sea of Marmara, and in the shallower zone between the Tekirdag and Central basins (Çagatay et al, 2000;Reichel and Halbach, 2007;Vidal et al, 2010). The different ages proposed are in agreement and a 11-7.5 kyr BP period (cal 14 C without reservoir correction) has been attributed to this particular episode.…”
Section: Background Sedimentationsupporting
confidence: 72%
See 3 more Smart Citations
“…The highest values characterize the 1380-980 cm so-called "sapropelic" interval. This organic matter enrichment has been previously reported in the different basins of the Sea of Marmara, and in the shallower zone between the Tekirdag and Central basins (Çagatay et al, 2000;Reichel and Halbach, 2007;Vidal et al, 2010). The different ages proposed are in agreement and a 11-7.5 kyr BP period (cal 14 C without reservoir correction) has been attributed to this particular episode.…”
Section: Background Sedimentationsupporting
confidence: 72%
“…According to their radiocarbon dating, this change occurred at 13 cal kyr BP (before present). Vidal et al (2010) concluded on a slightly different scenario: beginning with the Aegean influence at 14.7 cal kyr BP, the progressive increase of the mixing, lasting 2 kyr, and followed at 12.8 cal kyr BP by an increase of terrigenous continental organic material. They relate the latter to the beginning of Younger Dryas (YD).…”
Section: The Nonmarine To Marine Transition -Age and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, to the south, the hydrology of the BS was also strongly affected by the cyclic drainage of Lake Disna. The increase in runoff due to repeated seasonal floods over four successive periods of ∼220 y raised the BS water level by around 100 m, until the sill of the Bosphorus Strait was reached (12,13,16,44,45), leading to the flooding of the vast northwestern shelf of the BS basin and the attendant drastic retreat of the coastline (SI Text). The resulting outflow of BS waters into the northeastern Mediterranean basins altered the hydrology of both the Marmara Sea (45) and the Aegean Sea (46,47).…”
Section: Regional Climate Forcingsmentioning
confidence: 99%